Thermochromic and acidochromic properties of polymer films doped with pyridyl-β-diketonate boron(III) complexes. (June 2020) - Jiménez, Raquel; Duarte, Frederico; Nuti, Silvia; Campo, José A.; Lodeiro, Carlos; Cano, Mercedes; Cuerva, Cristián
Abstract: A novel family of organoborane complexes based on pyridyl-β-diketonate ligands has been synthesised, and their colorimetric and luminescence behaviour studied both in solution and in the solid state. The compounds behave as fluorescent materials, emitting a bluish light with high quantum yields of the order of 0.5–0.7. Although organoboranes usually show an aggregation-caused quenching effect in the solid state, the compounds described here maintain their emissive properties in the condensed state. Taking into account the ability of these emitters to act as dyes, several polymer thin films doped with these dyes have been fabricated. Interestingly, the new materials not only present fluorescence properties but also thermochromism and acidochromism. On the one hand, the increase of temperature causes the establishment of new intermolecular interactions between the boron(III) complexes and the polymer matrixes, which generate disturbances in the fluorescence emission. On the other hand, the protonation of the pyridyl nitrogen atom occurs in highly-acidic environments and causes a red-shift in the emission band that can be observed even with the naked eye. The application of these polymer materials as temperature and acid sensors is presented in this work. Graphical abstract: Image 1 Highlights: The difluoride boron compounds behave as luminescent materials. They can be used as dyes to fabricate smart polymer films. The boron(III)-doped polymers exhibit thermochromism and acidochromism. The fluorescent response can be observed with the naked eye.